Sediment acidification and temperature increase in an artificial CO2 vent. (February 2021) - de Beer, Dirk; Lichtschlag, Anna; Flohr, Anita; van Erk, Marit Rianne; Ahmerkamp, Soeren; Holtappels, Moritz; Haeckel, Matthias; Strong, James
Highlights: A mechanistic explanation is provided for the observed CO2 loss in the sediments. Reactions of CO2 with the sediment lead to significant heating. The observations were modeled including reactions and losses due to lateral transport. CO2 leakage will lead to very local effects. Abstract: We investigated the effect of an artificial CO2 vent (0.0015−0.037 mol s −1 ), simulating a leak from a reservoir for carbon capture and storage (CCS), on the sediment geochemistry. CO2 was injected 3 m deep into the seafloor at 120 m depth. With increasing mass flow an increasing number of vents were observed, distributed over an area of approximately 3 m. In situ profiling with microsensors for pH, T, O2 and ORP showed the geochemical effects are localized in a small area around the vents and highly variable. In measurements remote from the vent, the pH reached a value of 7.6 at a depth of 0.06 m. In a CO2 venting channel, pH reduced to below 5. Steep temperature profiles were indicative of a heat source inside the sediment. Elevated total alkalinity and Ca 2+ levels showed calcite dissolution. Venting decreased sulfate reduction rates, but not aerobic respiration. A transport-reaction model confirmed that a large fraction of the injected CO2 is transported laterally into the sediment and that the reactions between CO2 and sediment generate enough heat to elevate the temperature significantly. A CO2 leak will have only local consequences for sediment biogeochemistry, and only a small fraction of the escaped CO2 will reach the sediment surface.